Tunable electrorheological characteristics and mechanism of a series of graphene-like molybdenum disulfide coated core–shell structured polystyrene microspheres. Issue 31 (10th March 2016) - Wang, Xiaowen; Qian, Xing; Jiang, Xiancai; Lu, Zhen; Hou, Linxi
Abstract : Core–shell structured molybdenum disulfide (MoS2 ) coated polystyrene (PS) microspheres are synthesized with the help of hexadecyl trimethyl ammonium bromide (CTAB) through negative–positive electrostatic attraction. Abstract : Core–shell structured molybdenum disulfide (MoS2 ) coated polystyrene (PS) microspheres are synthesized with the help of hexadecyl trimethyl ammonium bromide (CTAB) through negative–positive electrostatic attraction. The morphology of the composite particles is studied by scanning electron microscopy (SEM), which apparently provides evidence of MoS2 -coated PS. The microspheres' structure and chemical components are investigated by X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy, respectively. The MoS2 /PS composite particles show better thermal stability than PS according to thermogravimetric analysis (TGA). Novel electrorheological (ER) fluids based on the MoS2 /PS composite dispersed in silicone oil are prepared and further examined by a rotational rheometer in a controlled shear rate mode under various electric field strengths. The influence of factors such as the electric field strength, the particle sizes, the proportions of the MoS2 /PS composite and the functional groups on the surface of PS on ER properties is investigated. The related mechanism of these effects on ER behaviors is also analyzed in detail, aiming to find whether the graphene analogue MoS2 is superior to graphene when making them into ER fluids. MoS2 has reversible and tunable electrorheological characteristics and can transform its phase from a liquid-like to a solid-like state when exposed to an external electric field.